A gestão de resíduos sólidos e conscientização ambiental como ação educativa no contexto escolar no município de Santa Luzia do Pará. - SOUSA, Suzane de Cássia Gomes de (2023)
Issues linked to environmental awareness in the school environment are undoubtedly one of the best ways to form ecological subjects. This work seeks to reflect on the importance of environmental education for the management ofsolid waste and its disposal, since a large part of environmental imbalances are related to incorrect conduct and habits, which can be changed through simple actions in everyday life. The methodology used was qualitative and quantitative and the data used are the results of observation of the EMEF Odilon Camurça school. Our theoretical framework was based on the National Solid Waste Policy (2010), National Environmental Education Policy (1999), and other authors who reinforce the importance of environmental education for the topic of solid waste management. From the incursions carried out, it was possible to see that the debate on solid waste management still needs to advance a lot in the school environment, and that this waste is reused in other activities by teachers. Finally, we can conclude that environmental education contributes to the formation of conscious citizens, able to decide and act in the socio-environmental reality in a way committed to life, to the well-being of each person and society.